On handbag recognition and recommendation - Wang, Yan (2016)
From Google to Pinterest, multimedia search engines such as Google Goggles deliver a wealth of visual information related to the search query. It recognizes and provides useful information when pointing the mobile phone camera at a business card, a book, a painting, a famous landmark, or a barcode. Vision-based techniques try to perceive and understand images by learning from the ability of human vision. Developing such techniques remains an ongoing challenge for computers.